2021
DOI: 10.1111/tpj.15514
|View full text |Cite
|
Sign up to set email alerts
|

Proteins associated with the Arabidopsis thaliana plastid rhomboid‐like protein RBL10

Abstract: Rhomboid-like proteins are intramembrane proteases with a variety of regulatory roles in cells. Though many rhomboid-like proteins are predicted in plants, their detailed molecular mechanisms or cellular functions are not yet known. Of the 13 predicted rhomboids in Arabidopsis thaliana, one, RBL10, affects lipid metabolism in the chloroplast, because in the respective rbl10 mutant the transfer of phosphatidic acid through the inner envelope membrane is disrupted. Here we show that RBL10 is part of a high-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Hence, it can be hypothesized that Cg2767 – perhaps together with Cg0049 – shapes the proteome at both temperatures in a similar way; yet at 40°C the effect is bigger. No results from other bacteria confirming the role of rhomboids in heat stress adaptation are available, but it has been found that expression of the plant rhomboid AtRBL10 increases during heat shock and 29% of its expression-correlated genes function in response to heat ( Knopf and Adam, 2012 ), and its gene disruption affects lipid composition due to a potential role in a lipid synthesis complex assembly ( Lavell et al, 2021 ). It remains to be verified if bacterial rhomboids exert related functions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it can be hypothesized that Cg2767 – perhaps together with Cg0049 – shapes the proteome at both temperatures in a similar way; yet at 40°C the effect is bigger. No results from other bacteria confirming the role of rhomboids in heat stress adaptation are available, but it has been found that expression of the plant rhomboid AtRBL10 increases during heat shock and 29% of its expression-correlated genes function in response to heat ( Knopf and Adam, 2012 ), and its gene disruption affects lipid composition due to a potential role in a lipid synthesis complex assembly ( Lavell et al, 2021 ). It remains to be verified if bacterial rhomboids exert related functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the plastid rhomboid-like protein RBL10 has also been found to form interactomes in the inner chloroplast envelope membrane with many chloroplast proteins, including ACP4 and CTI1 (Lavell et al, 2021). RBL10 is likely involved in chloroplast lipid metabolism since its loss of function dramatically affects monogalactosyldiacylglycerol biosynthesis in A. thaliana (Lavell et al, 2019(Lavell et al, , 2021. However, the precise structural characteristics of RBL10 interactions with ACP4 or CTI1, and the relevance of these interactions in terms of lipid metabolism remain largely unknown and are currently under further investigation.…”
Section: Other Protein Interactomes Involved In Lipidrelated Pathwaysmentioning
confidence: 99%
“…Recently, the plastid rhomboid-like protein RBL10 has also been found to form interactomes in the inner chloroplast envelope membrane with many chloroplast proteins, including ACP4 and CTI1 (Lavell et al, 2021). RBL10 is likely involved in chloroplast lipid metabolism since its loss of function dramatically affects monogalactosyldiacylglycerol biosynthesis in A. thaliana (Lavell et al, 2019(Lavell et al, , 2021.…”
Section: Other Protein Interactomes Involved In Lipidrelated Pathwaysmentioning
confidence: 99%
“…RBL10 is part of a high‐molecular weight complex of 250 kDa that also contains acyl carrier protein 4 (ACP4) and carboxyltransferase interactor 1 (CTI1). The acp4 and rbl10 mutants of Arabidopsis exhibit lower C16:3 FA levels in MGDG (Lavell et al ., 2021).…”
Section: Metabolism Of Plant Lipidsmentioning
confidence: 99%